Design and construction of a portable neutron radiographic camera - Akbulut, Dursun. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
The subject of this thesis is to provide a coherent picture of the components and methods involved i n neutron radiography, that is by now a proven technique in non destructive testing. Having presented a detailed picture of the prioriples related to neutron radiography, design and construction of a neutron radiographic camera, containing a 241 Am - Be neutron source has been developed. In ths first chapter the methods and companents of a neutron radiography unit has been described. In chapters two, three, four and five the components of neutron radiographic facility has been considere in a detailed manner. In chapter six the design of a neutron radiographic camera has been considered and some theoretical methods have been applied to determine the thermal neutron distrition and the doserates. Finally, construct on of a neutron radiographic camera and discussion of prospects on this topic and applications have been presented in the last section.
Keywords: Neutron radiography.; Neutron sources.